Dividendo entre reputación y persistencia de ganancias; Dividend between reputation and earnings persistence - Juan Fernando Garrido Navia; Jesús-Ancizar Gómez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– Do the persistence-predictability of earnings and reputation, affects dividend policy? This study provides new elements to enrich the debate around the question. To this end, a data panel of companies listed in Latin America is structured with financial information obtained in the Datastream database and a corporate reputation ranking known as MERCO during the period between 2008 and 2016. Subsequently, the hypotheses are tested with an econometric study. Our econometric study is based on the model which Lipe (1990) estimates the return of a stock through the properties of the time series of profits, the interest rate used to discount expected future earnings, and the relative ability of earnings compared to alternative information to predict future earnings. Among the main findings we find that the measure of persistence increases the ratio of dividends on assets, but when you are in MERCO the result is negative. It is as if companies take advantage of appearing in the ranking to pay less dividends.
Keywords: G12; G35; 330; Dividend; reputation; earnings persistence; and predictability